The Analysis of Complications of Tuberculosis Sufferers Due to History of Drug Breakup in The Area of Puskesmas Puri Mojokerto Regency - Lutfi Wahyuni; Inna Octavia; Norma Cindy Erlina (STIKes Patria Husada Blitar, 2021)
Pulmonary TB disease is one of the priorities of eradication of infectious diseases. Early-stage drug breakup occurs if the patient does not take medication 2 months in a row or more before the treatment period is complete. Drug breakups result in patients being resistant to OAT (Anti-Tuberculosis Drugs) and can lead to complications. This study aimed to analyze the occurrence of complications of tuberculosis sufferers due to a history of drug breakup. The design in this study was Correlation Analytics with Retrospective approach methods. The population in this study was all TB sufferers who had a history of drug breakups and complications. The sampling technique in this study was Non-Probability Sampling with purposive sampling type. The sample was 30 respondents. The instruments were interview for the history of drug breakup and patient treatment cards and observation and status of patient as the instruments of complications. Spearman Rho test results showed that value = 0.055 or more than Î± (0.05) which meant there was no correlation between the history of drug breakup with complications of tuberculosis. Based on this study, it could be concluded that the complications of tuberculosis that occur not only because of drug breakup factors but can be due to the spread of increasingly widespread germ infections, the immune system of the sufferers who are lacking, tuberculosis concomitant diseases, nutritional status of tuberculosis sufferers, and also knowledge from TB sufferers who lack the awareness to maintain health.